The 'Rock 'n' Fossil Road Show:': An Enduring Earth Science Educational Outreach Initiative in Calgary, Alberta - MacNaughton, Robert; Nowlan, Godfrey; McCracken, Alexander; Fallas, Karen (Geoscience Canada, 2017)
Since 2004, the Calgary office of the Geological Survey of Canada has been holding 'Rock ‘n' Fossil Road shows' at Calgary Public Library branches, in partnership with the Alberta Science Network and the Alberta Palaeontological Society. These now-annual earth science education outreach events have given more than 3700 people of all ages the opportunity to view, examine, and learn about GSC-Calgary's collection of rocks, minerals, and fossils (including many museum quality pieces), have their own samples and collections identified by experts, and gain a better understanding of local and regional geology. This article describes what goes into organizing these events, reviews their evolution, and discusses reasons for their enduring success. The 'Road Show' approach can be viable in a range of settings and may be a good educational outreach option for research institutes with collections of interesting geological specimens and a critical mass of interested staff.